Physical properties and GC/MS analysis of pyrolysis oil from tire and plastic waste (HDPE/high-density polyethylene and PP/polypropylene) - Al Buchori Nur Fajar; Niken Safitri; Khoirina Dwi Nugrahaningtyas (Jurnal Rekayasa Proses, 2024)
Pyrolysis is an innovative technology that can convert various types of waste into high-value products. Pyrolysis Oil (PO) can be used as an alternative fuel. The objective of this research aims to determine the physical properties and the content of chemical compounds in the pyrolysis oil of waste tire and plastic, which are then compare to the characteristics of commercial fuel. Pyrolysis was carried at 350℃ for 4 hours using motorcycle tire and plastic waste (HDPE and PP) as raw materials. The result shows that the physical properties of PO HDPE C are similar to gasoline with a density of 0.807 g/mL, dynamic viscosity of 0.623 cP, and kinematic viscosity of 0.771 cSt. However, its calorific value is still very low. PO PP C has a calorific value almost comparable to commercial fuel of 38.24 MJ/kg. Meanwhile for PO tires, the properties unqualified characteristics of fuel. GC/MS analysis shows that PO Tires C1 has a high content of olefins and aromatic compound. PO HDPE C has a high content of paraffin and olefin compound. Pyrolysis oil of tires and plastic waste have the potential to be used as fuel. Pyrolysis conditions to produce PO with characteristics similar to fuel.